Solar Photovoltaic Powered Sailing Boat Using Buck Converter - Soumya Das; Pradip Kumar Sadhu; Nitai Pal; Gourav Majumdar; Saswata Mukherjee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The main objective of this paper is to establish technical and economical aspects of the application of stand-alone photovoltaic (PV) system in sailing boat using a buck converter in order to enhance the power generation and also to minimize the cost. Performance and control of dc-dc converter, suitable for photovoltaic (PV) applications, is presented here. A buck converter is employed here which extracts complete power from the PV source and feeds into the dc load. The power, which is fed into the load, is sufficient to drive a boat . With the help of matlab simulink software PV module and buck model has been designed and simulated and also compared with theoretical predictions.